Effects of estradiol on the JAK/STAT pathway and the expression levels of inflammatory cytokines in a gonococcal infection model - ZHENG Chunchan; ZHONG Li; LI Sirui; LIN Yingping; CHEN Rongyi (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To explore the effects of Estradiol (E2) on the JAK/STAT pathway and the expression levels of inflammatory cytokines in a mouse spleen mononuclear cell model of gonococcal infection. [Methods] Mononuclear cell suspension was obtained from 8-10-week-old female C57BL/6 mice. The cells were divided into 4 groups: blank control group, E2 group, Neisseria gonorrhoeae (Ng) group, and Neisseria gonorrhoeae+Estradiol (Ng + E2) group. Mononuclear cells in the blank group were incubated with 10% FBS + RPMI1640 medium, while cells in E2 group were incubated with 10%FBS+RPMI1640 medium+E2 solution. Mononuclear cells in the Ng group were cultured with 10% FBS + RPMI1640 medium + Ng lysate, and mononuclear cells in the Ng + E2 group were cultured with 10% FBS + RPMI1640 medium+Ng lysate+E2 solution. The number of mononuclear cells in each group was 2.0×107, and the final concentration of E2 was 108 mol/L. The Ng lysate was obtained by sonication of a Ng suspension in 1 mL of 2.0×107 CFU/mL. Real-time fluorescence quantitative PCR (RT-qPCR) was used to measure the expression levels of mRNA for IL-17A, IL-17F, IL-36α, IL-36β, and IL-36γ. Enzyme-linked immunosorbent assay (ELISA) was used to measure the expression levels of inflammatory cytokines in each group. Western blot was used to determine the levels of non-phosphorylated and phosphorylated JAK(1-3), Tyk2, and STAT(1-6) in each group. [Results] RT-qPCR and ELISA results showed that compared with the blank controls, the expression levels of proinflammatory cytokines (IL-17A、IL-17F、IL-36α、IL-36β、IL-36γ) in the Ng group were significantly up-regulated, while the expression levels of anti-inflammatory cytokines (IL-10、TGF-β) were significantly down-regulated. In contrast, the expression levels of proinflammatory cytokines in the Ng+E2 group were significantly down-regulated, while the expression levels of anti-inflammatory factors was significantly up-regulated compared with the Ng group. However, the expression levels of inflammatory cytokines did not differ significantly between E2 and blank group (P>0.05). Western blot results showed that the levels of phosphorylated JAK(1-3), Tyk2, and STAT(1-6) were significantly higher in the Ng group than in the blank control (P<0.01). Moreover, the levels of phosphorylated JAK(1-3), Tyk2, and STAT(1-6) were lower in the Ng+E2 than in the Ng group. The phosphorylated levels of JAK (1-3), Tyk2, and STAT (1-6) were comparable between the E2 and the blank group (P>0.05). [Conclusions] E2 can inhibit the phosphorylation of JAK(1-3), Tyk2, and STAT(1-6) and lower expression levels of proinflammatory cytokines, while up-regulating the expression levels of anti-inflammatory factors in a mouse spleen mononuclear cell model of gonococcal infection. E2 regulates the expression of inflammatory cytokines by modulating the JAK/STAT signaling pathway in a mouse spleen mononuclear cell model of gonococcal infection.